2016
DOI: 10.1186/s13068-016-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Steam explosion pretreatment of softwood: the effect of the explosive decompression on enzymatic digestibility

Abstract: BackgroundSteam explosion pretreatment has been examined in many studies for enhancing the enzymatic digestibility of lignocellulosic biomass and is currently the most common pretreatment method in commercial biorefineries. The information available about the effect of the explosive decompression on the biochemical conversion is, however, very limited, and no studies prove that the latter is actually enhanced by the explosion. Hence, it is of great value to discern between the effect of the explosion on the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(101 citation statements)
references
References 30 publications
6
95
0
Order By: Relevance
“…The increase in glucose yield from 5.1% in steam-treated wood to 9.8% in steam-exploded wood is a result of physical structural modification. Pielhop et al (2016) also observed 90% increase in digestibility of cellulose in steam exploded wood as compared to steam-treated wood. The chemical changes during the steam-treatment step (i.e., the hydrolysis of hemicelluloses and redistribution of lignin) increased the accessibility of enzymes to celluloses and resulted in greater cellulose hydrolysis.…”
Section: Resultsmentioning
confidence: 61%
“…The increase in glucose yield from 5.1% in steam-treated wood to 9.8% in steam-exploded wood is a result of physical structural modification. Pielhop et al (2016) also observed 90% increase in digestibility of cellulose in steam exploded wood as compared to steam-treated wood. The chemical changes during the steam-treatment step (i.e., the hydrolysis of hemicelluloses and redistribution of lignin) increased the accessibility of enzymes to celluloses and resulted in greater cellulose hydrolysis.…”
Section: Resultsmentioning
confidence: 61%
“…Alternatively, the pressure can also be released via a hand valve at the bottom of the reactor into a secondary tank. More details on the steam explosion system (steam generation and injection, removal of entrapped air, construction details and schematic drawing) can be found elsewhere [27]. …”
Section: Methodsmentioning
confidence: 99%
“…The biomass filter cake was not washed and its dry matter content was determined in duplicate. More details on the pretreatment procedure (preheating of reactor, time measurement, experiments without explosion) can be found elsewhere [27]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a genetically modified strain was developed to omit the detoxification process [15]. Another method is the organosolv method such as used on Oil Palm fronds [16], wheat straw [17] the steam explosion on sugarcane bagasse [18], sugarcane straw [19], wheat straw [20], spruce wood chips [21]. These methods partially hydrolyzes lignin bond with cellulose and hemicellulose but most of the hemicellulose are solubilized [22].…”
Section: Introductionmentioning
confidence: 99%